Circulating miRNAs as Potential Biomarkers in Myasthenia Gravis: Tools for Personalized Medicine - Sabre, Liis; Punga, Tanel; Punga, Anna Rostedt (Frontiers in Immunology, 2020)
Myasthenia gravis (MG) is an autoimmune disease caused by antibodies which attack receptors at the neuromuscular junction. One of the main difficulties in predicting the clinical course of MG is the heterogeneity of the disease, where disease progression differs greatly depending on the subgroup that the patient is classified into. MG subgroups are classified according to: age of onset [early onset MG (EOMG; onset ≤ 50 years) versus late onset MG (LOMG; onset >50 years]; presence of a thymoma (thymoma associated MG), antibody subtype [acetylcholine receptor antibody seropositive (AChR+), muscle specific tyrosine kinase antibody seropositive (MuSK+)], or presence of antibodies against low-density lipoprotein receptor-related protein 4 (Lrp4) or agrin as well as clinical subtypes (ocular versus generalized MG). The diagnostic tests for MG such as antibody titers, neurophysiological tests and objective clinical fatigue score, do not necessarily reflect disease progression. Hence, there is a great need for reliable objective biomarkers in MG to follow the disease course as well as the individualized response to therapy towards personalized medicine. In this regard, circulating microRNAs (miRNAs) have emerged as promising potential biomarkers due to their accessibility in body fluids and unique profiles in different diseases, including autoimmune disorders. Several studies on circulating miRNAs in MG subtypes have revealed specific miRNA profiles in patient sera. In generalized AChR+ EOMG, miR-150-5p and miR-21-5p are the most elevated miRNAs, with lower levels observed upon treatment with immunosuppression and thymectomy. In AChR+ generalized LOMG, miR-150-5p, miR-21-5p and miR-30e-5p levels are elevated and decrease in accordance with clinical response after immunosuppression. In ocular MG, higher levels of miR-30e-5p discriminate patients who will later generalize from those remaining ocular. In contrast, in MuSK+ MG, the levels of the let-7 miRNA family members are elevated. Studies of circulating miRNA profile in Lrp4 or agrin antibody seropositive MG are still lacking. This review summarizes the present knowledge of circulating miRNAs in different subgroups of MG.